Scientific theoretical significance and interdisciplinary role of linguosemiotic models - Nurmatova Sadbarkhan Erkinovna (Euro Asian Journal Publishing, 2024)
the article describes the pragma-cognitive implementation of linguosematic models and their characteristics, the opinions of scientists, the concepts of cognitive linguistics, and information about cognitive pragmas.
Keywords: linguistics; pragma; scientific view; cognitive